Dynamic contracting with limited commitment and the ratchet effect - Dino Gerardi; Lucas Jóver Maestri (Theoretical Economics, 2020)
We study dynamic contracting with adverse selection and limited commitment. A firm (the principal) and a worker (the agent) interact for potentially infinitely many periods. The worker is privately informed about his productivity and the firm can only commit to short-term contracts. The ratchet effect is in place since the firm has the incentive to change the terms of trade and offer more demanding contracts when it learns that the worker is highly productive. As the parties become arbitrarily patient, the equilibrium outcome takes one of two forms. If the prior probability of the worker being productive is low, the firm offers a pooling contract and no information is ever revealed. In contrast, if this prior probability is high, the firm fires the unproductive worker at the very beginning of the relationship.
Keywords: D80; D82; D86; 330; Dynamic contracting; limited commitment; ratchet effect